(untitled) (Journal of Engineering, 2014)
The political situation experienced by Iraq before the events of 2003 that led to the collapse of infrastructure. rebuilding costs were estimated after 2003 by187(million USD) according to the estimates of the basic needs as stated in Five-Year Plan 2010-2014. The difficult in financing projects and the continuous demands for maintenance and operating cost, and working by contemporary styles in different countries, the strategic option is to adopt the government entering the private sector as a partner in the development process. Since public _private partnership (PPP’s) is at a germinating stage of development in Iraq, it has been studied the critical success factors(CSF’s) in the experiences of countries that have implemented the style (PPP’s) in infrastructure projects which can be ensured or controlled in some way and in the effective management of those already embarked upon . It should pave the way for enhanced decision making in the choice of suitable projects. The mainly aims of this paper are: 1- To highlight the importance and need of PPP‘s contracts in Iraq. 2- Establishing a model of CSF’s for infrastructure projects in Iraq. collected (87)success factors which characterized by the state directly in PPP’s projects consists of (8)main criteria(Privatization and investment Policy, Economical , Legal and political ,Financial and commercial, Administration and organizational ,Social and environmental ,Technical and Support , motives and guarantees of government) and found out (40) CSFs among them through questionnaire experienced in these projects to work to assess the standards and compare them and come to decisions by the decision maker, and therefore have a database of views experienced for use in other projects.